Oridonin Dose-Dependently Modulates the Cell Senescence and Apoptosis of Gastric Cancer Cells - Yiping Wang (Hindawi Limited, 2021)
Gastric cancer (GC) is the fourth most lethal cancer. Effective treatments are lacking, and our knowledge of the pathogenic mechanisms in play is poor. Oridonin from the Chinese herb Rabdosia rubescens exerts various anticancer activities. However, the dose-dependent effects of oridonin on human GC remain unclear. Here, we found that oridonin inhibited GC cell growth in a time- and dose-dependent manner. Low-dose oridonin induced GC cell cycle arrest at G0/G1 and cell senescence by suppressing the c-Myc-AP4 pathway and enhancing p53-p21 signaling. AP4 overexpression partly abrogated the oridonin-induced senescence of GC cells. High-dose oridonin induced apoptosis and autophagy, with the autophagy inhibitor BafA1 attenuating oridonin-induced apoptosis. Together, the findings indicate that oridonin at different doses modulates GC cell senescence and apoptosis; oridonin may thus usefully treat GC.